Host-Pathogen Interactions Mediating Pain of Urinary Tract Infection - Rudick, Charles N.; Billips, Benjamin K.; Pavlov, Vladimir I.; Yaggie, Ryan E.; Schaeffer, Anthony J.; Klumpp, David J. (The Journal of infectious diseases, 2010)
Background. Pelvic pain is a major component of the morbidity associated with urinary tract infection (UTI), yet the molecular mechanisms underlying UTI-induced pain remain unknown. UTI pain mechanisms probably contrast with the clinical condition of asymptomatic bacteriuria (ASB), characterized by significant bacterial loads without lack symptoms. Methods. A murine UTI model was used to compare pelvic pain behavior elicited by infection with uropathogenic Escherichia coli strain NU14 and ASB strain 83972. Results. NU14-infected mice exhibited pelvic pain, whereas mice infected with 83972 did not exhibit pain, similar to patients infected with 83972. NU14-induced pain was not dependent on mast cells, not correlated with bacterial colonization or urinary neutrophils. UTI pain was not influenced by expression of type 1 pili, the bacterial adhesive appendages that induce urothelial apoptosis. However, purified NU14 lipopolysaccharide (LPS) induced Toll-like receptor 4 (TLR4)-dependent pain, whereas 83972 LPS induced no pain. Indeed, 83972 LPS attenuated the pain of NU14 infection, suggesting therapeutic potential. Conclusions. These data suggest a novel mechanism of infection-associated pain that is dependent on TLR4 yet independent of inflammation. Clinically, these findings also provide the rational for probiotic therapies that would minimize the symptoms of infection without reliance on empirical therapies that contribute to antimicrobial resistance.